Penetapan dan Proyeksi Tingkat Suku Bunga Bank Indonesia (BI-Rate) Hubungannya dengan Laju Pertumbuhan Ekonomi Indonesia - Irwan, Lella N Q (Jurnal Trikonomika, 2012)
Since July 2005, the determination of the interest rate of Bank Indonesia (BI-rate) has been responded positively by national banks. The effect of Bank Indonesia monetary policy on interest rates and the real sector applies or valid at national and regional levels. The determination of which are often the adjustment of the interest rate can be seen as a signal for the market indicates the direction of the other interest rates movement, The increase or decrease of the BI-rate will affect the inter-bank interest rate and the time deposit interest rate that results the changes of the mortgage interest rates. Thus, the BI-rate could signify the government expectation of the banks to encourage the real sector to boost the economic growth in Indonesia. The purpose of this research is to understand the determination or the adjustment and the forecast of the BI-rate, also the causal relationship between the BI-rate and the economic growth rate in Indonesia. This research shows that, until 2015, the forecast of the BI-rate and the economic growth rate in Indonesia have the tendency to increase. Meanwhile, according to the results of causality test indicates that the BI-rate does not have a direct causal relationship with economic growth. Despite it is indicated that the BI-rate is going one-way relationship to the rate of economic growth in Indonesia, meaning that the BI-rate lead to economic growth while the economic growth can not directly push the changes of the BI-rate.